Untimely Punishment and Dubious Desert - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2002)
Discussions of punishment have always assumed (e.g.[4, pp. 80-5]) that there are no circumstances in which someone can be justifiably punished for a crime that he will commit. This assumption has been directly challenged by Christopher New’s apparent example of morally justified ‘prepunishment’ [7]. In a recent paper, Fred Feldman rejects the ‘received wisdom’1 that desert cannot precede its basis by giving apparent examples of ‘predeserved’ charity, reward and apology [3, pp. 71-75]. If there can be cases of predeserved punishment as well, then anyone who holds that it is morally justifiable to punish an offender if and only if he deserves it, must agree with New. For such desert theorists must say that since the offender predeserves punishment then it is morally right to prepunish him. Feldman himself however gives reasons why no legal authority should ever decide that someone predeserves punishment [3, pp. 76-78]. But a careful examination of New’s example shows that these reasons are inadequate. In any case, Feldman is committed to the different but undefended claim that there can be no cases of predeserved punishment. In fact the desert theorist has an excellent reason for defending this claim. Good reasons for saying that prepunishment is wrong are also available to the deterrence theorist. Given the correctness of our intuition that this is the right verdict, both theorists pass the test of New’s fantastic example. But the desert theorist passes it better, because the all the reasons available to the deterrence theorist for judging prepunishment wrong are subordinate to those of the desert theorist. Finally I argue that despite Feldman’s examples, there is no reason to think that there are any predeserts at all.